Risk Factors for Urinary Incontinence in Pregnancy: A Case Control Study - Caruso, Fernanda Borsatto; Schreiner, Lucas; Todescatto, Alexandra Damasio; Crivelatti, Isabel; Oliveira, Julia Monteiro de (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2020)
Objective Urinay incontinence (UI) is a major public health problem that can harm women in any period of life, including during the gestational period. Urinary incontinence during pregnancy has been studied because this condition can reduce the quality of life and interfere in several aspects of the maternal-fetal binomial. The aim of this study was to determine the prevalence of UI in nullipara pregnant women and to identify risk factors associated with UI in this population.Methods This is a case-control study in which we invited nullipara women between 12 and 20 weeks of pregnancy to participate in the research. They were asked to answer a specific questionnaire, write a 3-day bladder diary, and undergo a urogynecological evaluation including pelvic organ prolapse quantification (POP-Q), empty stress supine test (ESST), and pelvic floor muscle assessment.Results A total of 70 out of 73 patients accepted to participate in the study, and the prevalence of UI in this population was 18.3%. Tobacco use was identified as an independent risk factor for UI in pregnant women (odds ratio 8.0). All other factors analyzed were not significantly associated to UI in pregnancy.Conclusion Urinary incontinence can be a major problem in pregnancy. We identified the use of tobacco as a risk factor for developing UI in pregnancy, which provides an extra reason to encourage patients to quit smoking.
Keywords: urinary incontinence; pregnancy; pelvic floor; tobacco use